DIMENSI KEPUASAN KOMPENSASI DAN KOMITMEN KERJA PEGAWAI DINAS PERTANIAN KABUPATEN BURU SELATAN - OYIHOE, ARIFIN TAPI (Fakultas Ilmu Sosial dan Ilmu Politik, 2020)
This study aims to determine the effect of compensation satisfaction on employee workcommitments. This type of research is explanatory research. The population in this study wereall permanent employees of Agriculture Services of South Buru Regency as many as 124.Determination of the sample of 50 people determined by simple random sampling. Data wereanalyzed by multiple regression.The results showed that the material compensation factor (X1),social compensation (X2) and activity compensation (X3) affected the work commitment ofemployees with a large influence value of 98.5%; where the activity compensation factordominantly influences the work commitment of Agriculture Services of South Buru Regencyemployees, with the largest partial r2 value of 64.8%.